Prothrombin/thrombin and the thrombin receptors PAR-1 and PAR-4 in the brain: Localization, expression and participation in neurodegenerative diseases - Sokolova, Elena; Reiser, Georg (Thrombosis and Haemostasis, 2008)
Emerging evidence demonstrates that thrombin exerts physiological and pathological functions in the central nervous system. Both prothrombin and its active form thrombin have been detected locally in the brain. The cellular functions of thrombin are mainly regulated by G protein-coupled protease-activated receptors (PARs). Thrombin can signal via PAR-1, PAR-3 and PAR-4. Some neurological diseases (e.g. Alzheimer’s disease or Parkinson’s disease) are characterized by increased levels of both active thrombin and PAR-1. This indicates that thrombin and its receptor may be closely involved in the development of neurodegenerative processes. The role of thrombin in brain injury can be either protective or deleterious, depending on the concentration of thrombin. Thrombin at high concentrations exacerbates brain damage. In contrast, low concentrations of thrombin rescue neural cells from death after brain insults. Also thrombin preconditioning has neuroprotective effects. Therefore, thrombin and thrombin receptors represent novel therapeutic targets for treating neurodegenerative diseases.
Keywords: Thrombin; PAR; central nervous system; neurodegeneration; neuroprotection